Funeral Meal in Scythian Burial Rite (Case Study of Northern Azov Region, 5th—4th Centuries BC) - Demina, A.D. (Археологія, 2023)
In the article the author investigates the Scythian funerary practices in the Northern Azov region, focusing on the role of food offerings and animal sacrifice. In the study the relationship between food remains in personal burial spaces and communal feasting at the burial mound surface are highlighted.